Building Religious Character and Social Concern for the Students of Madrasah Aliyah Darus Syifa’ Kudus Perspective of Sheikh Nawawi Al-Jawi - Subaidi; Saiful Hadi; Junaidi Arsyad; Faris Nur Khulafa; Abdulaziz Kaluape (TADRIS: Jurnal Pendidikan Islam, 2025)
This research describes building religious character and social concern for the students of Madrasah Aliyah Darus Syifa’ Kudus from the perspective of sheikh Nawawi al-Jawi. This research uses a qualitative approach with a descriptive type. Data collection techniques in this research are through observation and interviews. Meanwhile, the data analysis technique is carried out by data reduction, data presentation and drawing conclusions. The results of this study conclude that: first, religious character building for children through the delivery of the book material ‘Nashâih al-’Ibâd’ and the application of the essence of religious character education values is carried out through several activities including: a) praying before learning, b) tahfidz and tahsin al-Qur'an, c) dhuha prayer, d) congregational prayer. Second, social care character building through distributing aid to flood victims in Karanganyar Village, Demak Regency.